The influence of online sexual objectification experience on female college students’ disordered eating: the mediator of body surveillance and the moderator of physical exercise - Ting Zhang; Fengqing Jiang; Xin qi He (Journal of Eating Disorders)
Abstract Background Previous studies have shown that sexual objectification experience is closely related to eating disorders in adolescent female students, but the mechanisms and conditions under which online sexual objectification experience influences disordered eating in female college students need to be further explored. Therefore, this study aimed to explore the mediating and moderating variables of the relationship between online sexual objectification experience and disordered eating, and to provide suggestions for the prevention of disordered eating among female college students. Methods A total of 651 female college students were tested with Online Sexual Objectification Experience Scale, Body Surveillance Scale, Physical Exercise Scale and Disordered Eating Scale. The mediating role of body surveillance and the moderating role of physical exercise were examined using the latent structural equation approach and Model 15 in version 3.5 of the Process macro program, respectively. Results Online sexual objectification experience, body surveillance, and female college students’ restrictive eating, emotional eating, and exogenous eating were significantly and positively correlated with each other; body surveillance mediated the relationship between online sexual objectification experience and female college students’ restrictive eating, emotional eating, and exogenous eating, respectively; physical exercise significantly and negatively moderated the relationship between online sexual objectification experience and female college students’ restrictive eating, and the higher the level of physical exercise, the lower the predictive effect of online sexual objectification experience on female college students’ restrictive eating. Conclusions Body surveillance mediated the relationship between online sexual objectification experience and disordered eating among female college students, and physical exercise only moderated the relationship between online sexual objectification experience and restrictive eating among female college students.